Water and Sanitation Services : Achieving Sustainable Outcomes with Indigenous Peoples in Latin America and the Caribbean - World Bank Group (World Bank, Washington, DC, 2016)
Indigenous peoples in Latin American and the Caribbean (LAC) are 10 to 25 percent less likely to have access to piped water and 26 percent less likely to have access to improved sanitation solutions than the region’s non-indigenous population. Historically, Indigenous peoples have been marginalized from the development process in their own countries and still suffer discrimination from the mainstream societies today. Oftentimes, Indigenous territories are overlooked or avoided by Water Supply and Sanitation (WSS) project planners and proponents given their lack of understanding of how to engage or carry out projects in collective or semi-autonomous Indigenous territories, the remoteness of these areas, and the high associated per capita cost of a potential operation, among other reasons. The significant gap in Indigenous peoples’ access to WSS services, a basic human right that is closely linked to economic and social wellbeing, alongside the lack of established tools in the sector to guide engagement in Indigenous territories, motivated the creation of this Toolkit. The objective of the Toolkit is to provide practical guidance and operational tools to improve the inclusion of, engagement with, and delivery of sustainable WSS services to Indigenous peoples in LAC in order to permanently close the WSS service gap. The Toolkit summarizes the findings of interviews, consultations, and field visits carried out by a multi-sector, multi-national World Bank Team in 37 Indigenous communities located in urban, peri-urban and rural areas in seven LAC countries where the World Bank or other development actors had implemented WSS projects with Indigenous peoples.